EFEKTIVITAS KEBIJAKAN HARGA ECERAN TERTINGGI (HET) DAN RANTAI PASOK BERAS MEDIUM DI PROVINSI LAMPUNG - Putri, Nadya; Ismono, Raden Hanung; Murniati, Ktut (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
Indonesia is a country that consumes and produces rice, so rice is a primary need in Indonesia. The government stipulates the highest retail price (HET) of rice policy to maintain the stability of rice price. The purposes of this study are to fin out the effectiveness of rice HET policy in Lampung Province, to analyze the impacts of thepolicy stipulation, and to find out the difference between medium rice supply chains before and after the HET Policy. This research uses quantitative and qualitative descriptive method. Data collection techniques used were interviews using questionnaires and also observation. The results of this study were the policy of medium rice HET has not been effectively implemented Lampung Province with price difference of Rp1.663,00. This caused no impact on the farmers, distributors, retail traders, and consumers. In the previous study, the medium rice supply chain flow in Lampung Province was infour marketing channels while in the current study was in six marketing channels. Keywords: effectiviness, HET, rice, supply